v=(5X-4)(X+4)(2X-1)

Simple and best practice solution for v=(5X-4)(X+4)(2X-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v=(5X-4)(X+4)(2X-1) equation:


Simplifying
v = (5X + -4)(X + 4)(2X + -1)

Reorder the terms:
v = (-4 + 5X)(X + 4)(2X + -1)

Reorder the terms:
v = (-4 + 5X)(4 + X)(2X + -1)

Reorder the terms:
v = (-4 + 5X)(4 + X)(-1 + 2X)

Multiply (-4 + 5X) * (4 + X)
v = (-4(4 + X) + 5X * (4 + X))(-1 + 2X)
v = ((4 * -4 + X * -4) + 5X * (4 + X))(-1 + 2X)
v = ((-16 + -4X) + 5X * (4 + X))(-1 + 2X)
v = (-16 + -4X + (4 * 5X + X * 5X))(-1 + 2X)
v = (-16 + -4X + (20X + 5X2))(-1 + 2X)

Combine like terms: -4X + 20X = 16X
v = (-16 + 16X + 5X2)(-1 + 2X)

Multiply (-16 + 16X + 5X2) * (-1 + 2X)
v = (-16(-1 + 2X) + 16X * (-1 + 2X) + 5X2 * (-1 + 2X))
v = ((-1 * -16 + 2X * -16) + 16X * (-1 + 2X) + 5X2 * (-1 + 2X))
v = ((16 + -32X) + 16X * (-1 + 2X) + 5X2 * (-1 + 2X))
v = (16 + -32X + (-1 * 16X + 2X * 16X) + 5X2 * (-1 + 2X))
v = (16 + -32X + (-16X + 32X2) + 5X2 * (-1 + 2X))
v = (16 + -32X + -16X + 32X2 + (-1 * 5X2 + 2X * 5X2))
v = (16 + -32X + -16X + 32X2 + (-5X2 + 10X3))

Combine like terms: -32X + -16X = -48X
v = (16 + -48X + 32X2 + -5X2 + 10X3)

Combine like terms: 32X2 + -5X2 = 27X2
v = (16 + -48X + 27X2 + 10X3)

Solving
v = 16 + -48X + 27X2 + 10X3

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Simplifying
v = 16 + -48X + 27X2 + 10X3

See similar equations:

| 4.8+x-5=3.6 | | (2n+7)(6n+7)=0 | | 7/12-4/9= | | (-3x)-9=-27 | | 2x-5(-0.25)=1 | | -5x+9=-4x+1 | | 16=-5+7r+7 | | 8/15÷-4/9= | | log[2](12x)-log[2](5x^2)=6 | | 3t^2-7t-20=10 | | 5(1+8n)=40+5n | | 1/3x3= | | (u-5)(3u-5)=0 | | 8/15÷-4/9 | | xty=0 | | 3(2x-3)-2(x-4)= | | 1000(7.48q+14.76)=100(3.91-4.25q) | | n+5n=-4 | | (3m-8)(2m-9)=0 | | 8x-6x-25=-10 | | -m^2+m+6=0 | | -3(1.15)+3y=6 | | -g+2(3+9)=4(g+1) | | 4/5n-k/5n | | f(x)=2x^3-4x^2-10x+20 | | 3(w+2w)+(5-2)*4+14w= | | 6+-3y-6y=-15 | | 0.2(600-2.4x)=3.7(3x-3000) | | -22/35*(-15/-33) | | (w-6)(8w+9)=0 | | 30x+20=36+28x | | 5,880/3000 |

Equations solver categories